2015
DOI: 10.1186/s12894-015-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

High pressure balloon dilation for vesicourethral anastomotic strictures after radical prostatectomy

Abstract: BackgroundVesicourethral anastomotic stricture (VAS) is a rare but serious complication following radical prostatectomy (RP), and various types of managements for VAS have been proposed. We investigated the efficacy of transurethral balloon dilation in the management of VAS after RP.MethodsA total of 128 consecutive patients underwent open RP at our hospital between 2008 and 2013; of these, 10 patients (7.8 %) developed VAS. Transurethral balloon dilation was performed in all 10 patients, using a high pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…45 At a mean follow-up time of 24 months, Ishii et al reported a 100% success rate after 1–2 dilations, using a high-pressure balloon catheter that consists of a 6-French (Fr) open lumen, blunt-tip catheter, and 6 cm long balloon that inflates fully to 30 Fr at a maximum inflation pressure of 30 ATM. 46…”
Section: Managementmentioning
confidence: 99%
“…45 At a mean follow-up time of 24 months, Ishii et al reported a 100% success rate after 1–2 dilations, using a high-pressure balloon catheter that consists of a 6-French (Fr) open lumen, blunt-tip catheter, and 6 cm long balloon that inflates fully to 30 Fr at a maximum inflation pressure of 30 ATM. 46…”
Section: Managementmentioning
confidence: 99%
“…Tables 1 and 2 present the main characteristics of the included studies. Among these, there were 1 RCT,27 2 single-arm clinical trials,28 29 2 case‒control studies30 31 and 10 retrospective case studies 32–41…”
Section: Resultsmentioning
confidence: 99%
“…Vesicourethral anastomotic strictures (VUAS) are considered to be one of the most common complications following radical retropubic prostatectomy, with rates of up to 30%. [1][2][3][4] Retrospective studies have reported that the majority of VUAS present within the first 24 months following RRP with lower urinary tract symptoms such as reduced flow or retention of urine. 5,6 VUAS do not occur only after surgical interventions, but are highly associated with radiation therapy and ablative therapy for PC, with high-dose-rate (HDR) brachytherapy demonstrating the highest rate of stricture formation among radiation therapy modalities.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Among previous prostate surgery, postoperative catheterization time, intraoperative blood loss, oncologic outcome, number of anastomotic sutures and postoperative leakage, several other factors have been discussed as contributing risk factors for the development of VUAS. 1,3,9 Numerous clinical trials document the incidence of this common postoperative complication. 6,9 Etiology and risk factors for the development of anastomotic strictures remain controversial, causing patients to undergo transurethral resections of the anastomotic stricture, making VUAS a frequently recurrent problem that adversely affects patients' quality of life 4,6 and are also a relevant risk factor for post-prostatectomy incontinence.…”
Section: Introductionmentioning
confidence: 99%